Day 1 Wed, February 15, 2017 2017
DOI: 10.2118/185065-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock-Fluid Interactions in the Duvernay Formation: Measurement of Wettability and Imbibition Oil Recovery

Abstract: In this study, we evaluate the wettability of shale samples drilled in the Duvernay Formation, which is a source-rock reservoir located in the Western Canadian Sedimentary Basin (WCSB). We use reservoir oil and brine to conduct air-liquid contact angle and air-liquid spontaneous imbibition tests for wettability measurements. We characterize the shale samples by measuring pressure-decay permeability, effective porosity, initial oil and water saturations, mineralogy, total organic carbon (TOC) content, and condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Hence, kerogen may be hydrocarbon-wetting at high maturity, neutral-wetting at intermediate maturities, or even hydrophilic for organic surfaces of very low maturities. It was also found that the samples with high thermal maturity imbibe more oil and have more affinity to oil and vice versa. ,, …”
Section: Effect Of Thermal Maturity Of Organic Mattermentioning
confidence: 93%
See 2 more Smart Citations
“…Hence, kerogen may be hydrocarbon-wetting at high maturity, neutral-wetting at intermediate maturities, or even hydrophilic for organic surfaces of very low maturities. It was also found that the samples with high thermal maturity imbibe more oil and have more affinity to oil and vice versa. ,, …”
Section: Effect Of Thermal Maturity Of Organic Mattermentioning
confidence: 93%
“…However, this includes a wide range of the clay content that is not conclusive for rough evaluation of the wettability of the shale. Begum et al 54 also expressed that the clay content may be a significant factor in controlling fluid imbibition, i.e., less oil imbibition with an increasing clay content.…”
Section: Effect Of Mineral Composition On Shale Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, some of tight oil reservoirs are water-wet, so imbibition can happen even if there is no surfactant in the fracturing fluid. However, in some mixed-wet or oil-wet reservoirs, surfactant is usually added into water or the fracturing fluid to promote imbibition by changing the wettability (Begum et al 2017;Alvarez et al 2017;Meng et al 2018;Huang et al 2020). In order to reflect this effect, the capillary force ratio of water to surfactant can be approximated using the Young-Laplace equation assuming constant pore diameter for water and surfactant imbibition,…”
Section: Simulation Of Forced Imbibition With High-pressure Soakingmentioning
confidence: 99%
“…And where are the major hydrocarbon flow pathways? Rock small‐scale features such as mineral complexity and microfractures can remarkably change the multi‐phase flow pattern in near‐fracture zones and throughout the formation, causing unexpected and sophisticated fluid flow behaviour in shales . To illustrate this, Figure demonstrates two SEM images of the Eagle Ford and Barnett shales.…”
Section: Workflow Of Numerical Simulationmentioning
confidence: 99%